The effect of photoinitiator type and filler load on physicochemical and mechanical properties of experimental light-cured resin cements through lithium disilicate ceramics of different shades and thicknesses - Strazzi-Sahyon, Henrico Badaoui [UNESP]; Hadis, Mohammed A.; dos Santos, Paulo Henrique [UNESP]; Palin, William M. (Elsevier, 2024)
Objective: This study investigated the influence of photoinitiator types on degree of conversion (DC), rate of polymerization (RP), flexural strength (FS), flexural modulus (FM), and light transmittance (LT) of filled and unfilled light-curable resin cements through different thicknesses and shades of lithium disilicate ceramics. Methods: Lithium disilicate ceramic discs (IPS Emax Press, background [0.0], 0.5, 1.0, 2.0, 3.0, and 4.0 mm, shades A1 and BL3) were prepared. Experimental resin-based cements [TEGDMA/BisGMA (50/50 mass%)] were prepared using either camphorquinone (CQ)/amine (0.44/1.85 mol%) or TPO (0.44 mol%)], and a micro and nanofiller loads of nil (unfilled); 40/10 mass%; and 50/10 mass%). Resin cements (0.2 mm thick) were placed on the lower surface of the ceramic specimens and light-activated for 30 s from the upper surface using a Bluephase Style curing light (exitance at tip: 1236 mW/cm2 ± 1.20). LT and distribution of irradiance through the ceramics were measured using a UV–vis spectrometer and a beam profile camera, respectively (n = 3). The DC and RP were measured in real-time using mid infrared spectroscopy in attenuated total reflectance (ATR) mode (n = 3). FS and FM were measured using a universal testing machine (n = 5). Statistical analyses were performed on LT, DC, RP, FS, and FM data using a general linear model, and supplementary ANOVA and post hoc Tukey multiple comparison test were also performed (α = .05). Results: Thicknesses, shades, photoinitiator type, and fillers load significantly influenced the optical and mechanical characteristics of the resin-based materials (p < 0.05). The BL3 shade ceramic provided higher values of DC, RP, FS, FM, and LT compared with the A1 shade (p < 0.05). Increasing ceramic thickness decreased the properties of the resin-based materials (p < 0.05). Generally, TPO improved mechanical properties of the resin cement compared with CQ (p < 0.05). Significance: The luting process of indirect restorations may be improved by using high molar absorptivity, more reactive, and more efficient photoinitiators such as TPO, as opposed to conventional CQ. The use of such initiator may allow the placement of thicker and more opaque indirect restorations.
Keywords: Camphorquinone; Ceramics; Degree of conversion; Light transmittance; Resin cements; TPO